Efektivitas Penggunaan Sistem Srikandi dalam Pengelolaan Arsip Dinamis di Dinas Perpustakaan dan Kearsipan Kabupaten Tulungagung - Putri, Nadia Arista; Handayani, Nurul Setyawati (Nur Science Institute, 2025)
The background of this research is based on the need of government agencies for an efficient, responsive, and digital-based archive management system in line with the demands of bureaucratic reform and the implementation of the Electronic-Based Government System (SPBE). The purpose of this study is to evaluate the effectiveness of the use of the Integrated Dynamic Archival Information System (SRIKANDI) at the Tulungagung Regency Library and Archives Office and the supporting and inhibiting factors for the use of the SRIKANDI system at the Tulungagung Regency Library and Archives Office. The approach used is descriptive qualitative with data collection techniques in the form of semi-structured interviews, direct observation, and documentation of three informants, namely the head of the archives division, the Dynamic Archives Sub-Division, and the Archivist. The data was analyzed using the Miles and Huberman model through reduction, presentation, and conclusion drawing. The research findings indicate that SRIKANDI has a positive impact on improving productivity, work efficiency, employee satisfaction, digital technology adaptation, and the system's sustainability in archive management. However, challenges such as network disruptions, limited human resources, and suboptimal system features remain. Overall, SRIKANDI has proven effective in supporting modern and sustainable dynamic archive management, contributing to administrative orderliness and improved public services.